Library research support for masters and PhD students at the University of Eswatini - Dlamini, Khosie Konkhekluhle (Department of Knowledge and Information Stewardship, 2021)
The changing academic and technological environment coupled with evolving research practices have greatly impacted the role played by academic libraries within the institutions they serve. This has sparked a global concern amongst academic libraries to re-evaluate their services as a means to aligning themselves to this new environment. As a result, academic libraries are transforming themselves and bringing about new services, particularly focussing on how they can enhance research output by providing support to researchers. Given this context, this study seeks to ascertain the extent of research support by University of Eswatini (UNESWA) Libraries for masters and PhD students at UNESWA. To address this objective, the following critical questions were generated: What are the current services being provided by UNESWA Libraries to support masters and PhD students at the University of Eswatini?; What are the library research needs of masters and PhD students at UNESWA?; To what extent are these needs being met by UNESWA Libraries?; and, If there are library research needs of masters and PhD students at UNESWA that are not being met by UNESWA Libraries, what research support services need to be put in place to address this deficiency? Schoombee's (2014) research lifecycle adapted for library research support was used as a supporting theoretical framework to guide the study. The study adopted a convergent parallel mixed methods approach within a pragmatism paradigm and a case study design. Academic staff members and librarians at UNESWA were purposively sampled whilst a census was conducted for all masters and PhD students at UNESWA. Data was collected using a structured paper-based questionnaire and semi-structured interviews. Quantitative data was analysed using the Statistical Package for the Social Sciences (SPSS) and qualitative data was analysed thematically (by content analysis). The study concludes, inter alia, that despite the various library research support services provided by UNESWA Libraries for masters and PhD students, an expanded suite of research support services to more fully meet UNESWA's masters and PhD students' library research needs, is required. The study recommends that UNESWA Libraries should utilise available technologies and incorporate additional research support services that speak to the research needs of digital age masters and PhD students.